Unlocking Economic Landscape: Understanding the Dynamics of Financial Challenges, Business Traits, Financial Resources, Growth Phases, Financial Accessibility, and MSME Performance - Masnila, Nelly; Febriantoko, Jovan; Mayasari, Riana; Ariyanti, Indri (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Ease of access to finance serves as a driving force for the development of entrepreneurship. Entrepreneurship, in turn, has the capability to stimulate the creation of new employment opportunities. Sound financial access is crucial for supporting the sustainability and growth of the Micro, Small, and Medium Enterprises (MSMEs) sector. The objective of this research is to delve deeper into the challenges faced by MSMEs in accessing finance and analyze its influence on the business performance of MSMEs. The survey for this research was conducted on 324 MSMEs in the South Sumatra Province. The sample selected used the quota sampling technique. The research framework was developed and tested using a Structural Equation Model (SEM). The research findings indicate that business traits, financial resources, and growth phases of MSMEs have a significantly positive impact on financial access, while financial challenges have a negative impact that hinders the growth of MSMEs and affects overall MSME Performance.